Optical transparency and electrical conductivity of intermediate filaments in Muller cells and single-wall carbon nanotubes - Khmelinskii, Igor (2020)
Presently we investigated the electrical conductivity and optical transparency of Muller cell intermediate filaments. For comparison, the same properties were also explored in the model system of single-wall carbon nanotubes. We report the method of separation and purification of porcine (Sus scrofa domestica) intermediate filaments, extracted from the retinal Muller cells. We also report experimental and theoretical methods of measurements and calculations of the resistivity and light transmission yield by the intermediate filaments and single wall carbon nanotubes. The measured resistivity values were (4.7 +/- 0.3) x 10(-4) and (2.8 +/- 0.2) x 10(-4) Omega.m(-1).cm(2) at 5 degrees C (278 K), for the intermediate filaments and single wall carbon nanotubes, respectively, being quite close to those of typical metals. We report a method for measuring the light energy transmission by these nanostructures. We found that they efficiently transfer excitation energy along their axis, with the light reemitted at their other end. The measured yields of transferred light energy were 0.50 +/- 0.03 and 0.26 +/- 0.02 for intermediate filaments and single wall carbon nanotubes, respectively (lambda(exc) = 546.1 nm